If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + -9 + y + 49 = 8y + 40 + -6y Reorder the terms: -9 + 49 + 3y + y = 8y + 40 + -6y Combine like terms: -9 + 49 = 40 40 + 3y + y = 8y + 40 + -6y Combine like terms: 3y + y = 4y 40 + 4y = 8y + 40 + -6y Reorder the terms: 40 + 4y = 40 + 8y + -6y Combine like terms: 8y + -6y = 2y 40 + 4y = 40 + 2y Add '-40' to each side of the equation. 40 + -40 + 4y = 40 + -40 + 2y Combine like terms: 40 + -40 = 0 0 + 4y = 40 + -40 + 2y 4y = 40 + -40 + 2y Combine like terms: 40 + -40 = 0 4y = 0 + 2y 4y = 2y Solving 4y = 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 4y + -2y = 2y + -2y Combine like terms: 4y + -2y = 2y 2y = 2y + -2y Combine like terms: 2y + -2y = 0 2y = 0 Divide each side by '2'. y = 0 Simplifying y = 0
| (e/f)(g/h) | | 4(x-1)=3(2x+6) | | -9x^2+15x+84=0 | | 7x+7=12+3 | | -3x^3+87x^2-162x=0 | | 5(2x+1)=2(X-3) | | F(x)=-16x^2+64 | | -2x^2-44x+46=0 | | 3(X-6)=2(2x+1) | | 3x-11=x+3# | | 3x-11=3+3 | | 2-1/5=5 | | 4x+1=8x+2 | | 3x^2y-5xy^2=0 | | x+0.6x=900 | | (x^2+2xy+y^2)-1= | | 2(2x+3)=X+7 | | 7a-14b= | | (a-b)x^2+(b-c)x+(c-a)=0 | | 41p=5208 | | 5x=64-3x | | 19(4)= | | 7=5 | | 4x+19=752 | | 4(x+19)=752 | | 5x^3-20x^2+15x=1 | | 19(x+4)=752 | | y-4/5=33/4 | | 7.5=x-6.5 | | y=10-(1/6)*6 | | y=10-(1/6)*4 | | y=10-(1/6)*3 |